Kontradiksi Pengaturan Tindak Pidana Korupsi dalam KUHP Baru dengan Rencana Pembangunan Jangka Panjang Nasional Tahun 2005-2025 - Rahman, Fathor (University of Merdeka Malang, 2024)
The Corruption Criminal Procedure Regulations contained in Law No. 1 of 2023 on the Code of Penal Law (New Penal Code) have degraded the spirit of suppression of corruption crimes, especially with regard to the concept of punishment and the criteria for sanctioning it, because the Corrupt Criminals Regulations in the Law No.1 of 2003 on the code of criminal law, do not strengthen the Act on the prevention of corrupt criminal proceedings that is specifically in force, but rather weaken the effect of imprisonment for corruption offenders in Indonesia. In this case, it is also evident that there is a disharmonization with the legal development plan, which is contained in the National Long-term Development Plan 2005-2025. This research uses normative legal research methods with a legal, comparative and conceptual approach. The results of this study show that The results of this research show that corruption cases are one of the obstacles to the smooth development of the Indonesian State as a whole, and with the fact that the regulation of criminal acts of corruption in the new Criminal Code does not create a spirit of eradicating criminal acts of corruption, the laws and regulations related to eradicating corruption still needs to be repaired and updated.